Handbook of research on redesigning the future of internet architectures - Boucadair, Mohamed; Jacquenet, Christian (Hershey, PA, USA : Information Science Reference, an imprint of IGI Global, 2015)
'This book covers some of the hottest topics currently being debated by the Internet community at large, including Internet governance, privacy issues, service delivery automation, advanced networking schemes, and new approaches to Internet traffic-forwarding and path-computation mechanics'--
Includes bibliographical references and index.
Keywords: Computer network architectures -- Research; Internet -- Security measures -- Research; Internetworking (Telecommunication) -- Standards -- Research